Efficacy of cisplatin in early stage cervical cancer with a long waiting period for surgery - Prapaporn Suprasert (2018)
This study was undertaken as a prospective trial to evaluate the efficacy and safety of pre-operative cisplatin for controlling the tumor volume of stage IB-IIA cervical cancer patients whose schedule for radical surgery was longer than 3 weeks. Between June 2004 and July 2005, 42 patients were recruited to enter the study. Seventy-five mg/m2 of cisplatin was administered for 1-2 courses. Cervical tumor volume was measured 1 day before chemotherapy and 1 day before the operation by using 3-dimensional ultrasound. Reduction of cervical tumor volume was noted in 76.2%of cases. The clinical stage, gross appearance of the tumor, histology and number of chemotherapy courses did not significantly affect chemo-responsiveness. The incidence of lymph node metastases was 16.3%. One patient experienced severe vomiting which could be controlled by ondansetron antiemetic. No severe hematologic or other non-hematologic toxicities were identified. In conclusion cisplatin is effective and safe for administration in a pre-operative setting for early stage cervical cancer patients whose surgical schedule is delayed more than 3 weeks.